Diagnosis of the means used by the Institution of Higher Education for the generation of regional capital (Revista Brasileira de Contabilidade e Gestão, 2019)
The competitive environment that organizations are facing requires that the response of their actions have as main elements the revenue and the profit. However, there are educational organizations that are configured as community, where involvement with the community is also a primordial element. This relationship with several actors enables the generation of regional social capital (CSR), an essential aspect for this type of organization. Thus, the study proposes to analyze how social capital can be generated by a Community Higher Education Institution (HEI) in order to contribute to regional development. For the development of the study, the method used was the qualitative and exploratory approach, using technical procedures of the type secondary sources, through two sets of articles collected from the databases EBSCO and SPELL, bibliographical surveys on the subject, content analysis and internal documents Of the organization studied. As results of this study are presented aspects that demonstrate the importance of a community HEI in the promotion of CSR, also confirming its mission as an actor in the contribution of regional development.
Keywords: Regional Capital Stock; Higher Education Institution; Vale do Taquari